A review of nutritional facts, production, availability and future aspects of coconut palm sugar - Asghar, Muhammad Tuseef (Longdom Publishing, 2021)
Coconut palm (Cocos Nucifera L.) sugar with its low GI value and micro and macro nutrition contents is focused in developed countries as a natural alternative to unhealthy cane sugar and more beneficial for farmers as compared with copra production and cane sugar production. Coconut palm sugar (CPS) is available in the forms of syrup, blocks and granular sugar. Granular CPS can be a better substitute for regular sugar as it would be convenient and healthy to use. CPS is important therapeutically as it is an antioxidant, antidiabetic, renal treatment, menstrual disorder treatment, and treatment for deficiencies of hemoglobin and vitamins. CPS production is less than demand due to lack of advanced production technologies. Coconut sap contains 12-15% sugar and very susceptible to spontaneous fermentation and converted to alcohol. It is necessary to utilize or process the sap as soon as possible. Traditional production is unhygienic, laborious and time-consuming keeps many coconut farmers away from CPS production even production of CPS can earn more economic benefits for local farmers. It can be produced traditionally by evaporation of coconut sap at 115oC to 120oC for 3 to 5 hours. Advanced techniques like vacuum drying, freeze drying, and spray drying etc. can also be used for hygienic but small in quantity and more costly production of CPS. Dry granulation may be a low-cost technique for mass production of granular CPS. It can be best stored at moisture content less than 2-4%.